2007
DOI: 10.1371/journal.ppat.0030046
|View full text |Cite
|
Sign up to set email alerts
|

ART Suppresses Plasma HIV-1 RNA to a Stable Set Point Predicted by Pretherapy Viremia

Abstract: Current antiretroviral therapy is effective in suppressing but not eliminating HIV-1 infection. Understanding the source of viral persistence is essential for developing strategies to eradicate HIV-1 infection. We therefore investigated the level of plasma HIV-1 RNA in patients with viremia suppressed to less than 50–75 copies/ml on standard protease inhibitor- or non-nucleoside reverse transcriptase inhibitor-containing antiretroviral therapy using a new, real-time PCR-based assay for HIV-1 RNA with a limit o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
273
5
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 302 publications
(312 citation statements)
references
References 32 publications
(36 reference statements)
30
273
5
1
Order By: Relevance
“…Our earlier studies revealed a highly significant association between low-level viremia at week 60 and baseline HIV RNA levels, as well as a lack of association of this viremia on therapy with treatment regimen, suggesting that persistent viremia arises from reservoirs of long-lived cells infected before the initiation of therapy (4). The model used to fit the biphasic decay in the current study provides a mechanism to estimate individual patient parameter values, allowing us to further evaluate this theory.…”
Section: Hiv-1 Persistence During Therapymentioning
confidence: 65%
See 3 more Smart Citations
“…Our earlier studies revealed a highly significant association between low-level viremia at week 60 and baseline HIV RNA levels, as well as a lack of association of this viremia on therapy with treatment regimen, suggesting that persistent viremia arises from reservoirs of long-lived cells infected before the initiation of therapy (4). The model used to fit the biphasic decay in the current study provides a mechanism to estimate individual patient parameter values, allowing us to further evaluate this theory.…”
Section: Hiv-1 Persistence During Therapymentioning
confidence: 65%
“…R eduction of HIV-1 RNA levels to Ͻ50 copies per ml is frequently achieved with combination antiretroviral therapy, but residual low-level viremia has been detected, using ultrasensitive assays, despite such therapy (1)(2)(3)(4)(5). The source and dynamics of this residual viremia are currently unknown.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Quelques exemples de molécules, à même de réactiver l'expression du virus et donc utilisables en vue d'une stratégie de purge des réservoirs, sont représentés en rouge : activateurs de la voie de la signalisation cellulaire menant à NF-B (prostatin), inhibiteurs des histones déacétylases (HDACi) et activateurs du complexe P-TEFb (HMBA, hexaméthylène bisacétamide). a permis de détecter une virémie résiduelle [11][12][13]. Le problème de l'origine de cette virémie résiduelle était à nouveau au centre des débats, et les tenants d'une réplication rési-duelle chronique à nouveau sur le devant de la scène.…”
Section: Le Problème Posé Par La Découverte D'une Virémie Résiduelleunclassified